A ROLE FOR CELLULAR IMMUNITY IN EARLY POSTPARTUM PERIOD - N. A. Panova; V. G. Skopichev (Медицинская иммунология, 2021)
The functioning of the secretory organs is closely related to the activity of the immune system. As is well known, this participation is manifested in the fact that at certain stages of activity, the lymphoid cells migrating to the organ can be involved in the regulation of secretion. In addition, the products of the immune system and even its cellular elements can become components of a number of secrets. Colostrum and milk contain a large number of cells of a wide spectrum (up to 1/3 of the volume), of which the number of lymphocytes is up to 16% of leukocytes. Lymphocytes, in an immunologically active form, entering the newborn’s body with colostrum, activate the cellular immunity system. The transport of lymphokinin mediators plays a certain role in this process. Microphages, T- and B-lymphocytes, penetrating through the intercellular spaces into the lymphoid layer of the intestine, transmit immunoreceptors to the prolymphocytes of the newborn, "armed" with their activity to recognize genetically foreign ones. The lymphocytes contained in colostrum are the cells of the immune system that provide cellular and humoral immunity. They are mainly represented by T-cells, B-cells and killer cells. Milk T-cells produce a full spectrum of immune regulatory proteins such as interferon, tumor necrosis factor alpha. These cells are the cells of the immune memory. Newborns who received the first portion of colostrum no later than an hour after birth are characterized by an increased number of leukocytes, more pronounced phagocytosis, which indicates the stimulation of hemo- and lymphocytosis. When carrying out transmission and scanning electron microscopy in the epithelial layer of the intestine, cellular elements were found that got there from the intestinal lumen. Microsections show how cells of a lymphoid nature, pushing apart the structures of the epithelial layer, bypass natural barriers and, at the same time, retain their physiological usefulness. The possibility of penetration of immunocompetent cells of the mother’s colostrum into the bloodstream of the young is proved using the natural label of the female’s cells – sex chromatin. Naturally, sex chromatin-labeled cells were sought in male newborns. The detection of colostrum cells in the intestinal wall and bloodstream of the young is approximately 25% in the blood, 1% in the lymph, and about 70% in the intestine. There is no doubt that the leukocytes of colostrum are of exceptional importance in creating immunity in newborn animals.